2016
DOI: 10.18178/ijesd.2016.7.10.875
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation Potentials of Selected Plants in Industrially Contaminated Soils

Abstract: Abstract-Waste discharges into River Challawa in Kano, Nigeria is posing serious environmental hazards. The present study was therefore designed to examine the potentials of Jatropha (Jatrophacurcas), Neem (Azadirachtaindica) and Baobab (Adansoniadigitata) for phytoremediation of some heavy metalsin the industrially contaminated soils of Challawain Kano, Nigeria. The plants were grown under hydroponic greenhouse conditions for thirteen weeks andlevels of metals in plants, soil and effluent water were determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
3
5
0
Order By: Relevance
“…However, the results showed that roots were found to accumulate considerable amounts of Zn than leaf and stem tissues compared to their levels in similar tissues of the control as depicted by fig 2. This results agrees with the findings of Abdullahi et al, 2016,Waziri et al, 2016, Wu et al, 2011and Ahmadpour et al, 2010, for the same plant. Zinc is an essential trace element required for plant growth and it is very important in many metabolic processes in plants (Ji et al, 2021).…”
Section: Bajopas Volume 14 Number 1 June 2021supporting
confidence: 93%
See 1 more Smart Citation
“…However, the results showed that roots were found to accumulate considerable amounts of Zn than leaf and stem tissues compared to their levels in similar tissues of the control as depicted by fig 2. This results agrees with the findings of Abdullahi et al, 2016,Waziri et al, 2016, Wu et al, 2011and Ahmadpour et al, 2010, for the same plant. Zinc is an essential trace element required for plant growth and it is very important in many metabolic processes in plants (Ji et al, 2021).…”
Section: Bajopas Volume 14 Number 1 June 2021supporting
confidence: 93%
“…Among the heavy metals, Cd is relatively mobile in the soil and can be toxic to both plants and animals (Rizwan et al, 2017). Results obtained showed that accumulation of Cd in J. curcas is found to be higher in leaf than both the stem and root tissues compared to their levels in similar tissues of the control as depicted by fig 4.This results agrees with the findings of Chang et al, (2014), Abdullahi et al, (2016) and Waziri et al, (2016) for the same plant. Uptake of Cd in plants is controlled by its concentration and bioavailability in soil which are influenced by soil properties .Cd is one of the most phytotoxic elements and does not have a known biological function in plants (Dobrikova et al, 2021).…”
Section: Bajopas Volume 14 Number 1 June 2021supporting
confidence: 90%
“…These values indicated higher availability and distribution of metals in soils contaminated with heavy metals in the three plant species which can be labeled as translocators of Cd, Cr, Cu, Fe, Mn, Ni, Pb and Zn based on TF>1. Heavy metal tolerance with high TF value have been suggested for phytoaccumulator of contaminated soils [42,43] and therefore these plant species can be used as phytoremediators for multi-metal contaminated soils.…”
Section: Resultsmentioning
confidence: 99%
“…These values indicated higher availability and distribution of metals in soils contaminated with heavy metals in the three plant species which can be labeled as translocators of Cd, Cu, andPb based on TF>1. Heavy metal tolerance with high TF value have been suggested for phytoaccumulator of contaminated soils [21,22] and therefore these plant species can be used as phytoremediators for multi-metal contaminated soils. Also the results revealed high bioaccumulation factors (BAF) of all the metals examined in the tissues.…”
Section: Resultsmentioning
confidence: 99%